Smart Switching Power Supply System for Evaporative Air Coolers - Almarzouq, Mohammed; Al-Somali, Ahmed; Al-Abdulkarim , Saud; Owes, Amr (Global Journal of Energy Technology Research Updates, 2022)
The energy consumption by residential air conditioners could cost about half of the total energy consumption of the building. A combination of conventional and renewable energy is still an emerging technology. Therefore, using solar photovoltaic panels to provide electricity to the air conditioner is a substantial application. This research shows the possibility of using photovoltaic panels as a power source for air conditioners in a sequence exchange with the conventional grid. A smart switching system has been offered to organize the power supply between the grid and solar panels. The photovoltaic panels have been connected to the conditioner across a power inverter module for adopting a reliable and accurate quantity of power supply to the conditioner unit. The smart switching system provides an intelligent connection between the solar power source and the grid, ensuring an uninterrupted electricity supply between the two power sources.